Light-front quark-meson coupling model - Krein, G. [UNESP]; Miller, G. A. (Elsevier, 2001)
We formulate a quark-meson coupling model for nuclear matter using light front variables. We present results for saturation properties of nuclear matter and in-medium nucleon properties. We also calculate the distribution function of the plus momentum carried by nucleons in nuclear matter. Our model predicts that vector mesons carry only 7% of the fraction per nucleon of the total plus momentum of the system.